2007
DOI: 10.2174/157340207779815563
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Relationship Between Hypertension and Albuminuria

Abstract: Albuminuria is the increased excretion of the serum protein albumin into the urine. Albuminuria is classically seen as an important diagnostic marker of declining kidney function, however, more recently albuminuria has also been implicated as a marker for cardiovascular and peripheral vascular disease indicating an important link between processes governing both cardiovascular and renal function. This review will discuss i) a common mechanism for albuminuria that accounts for albuminuria seen in hypertension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 126 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…In membranous nephropathy, subepithelial immune-complex deposition is present along the glomerular basement membrane. There is also some evidence suggesting that albuminuria is caused by defective tubular trafficking and degradation of albumin 1,2. It may be that in HCT patients, inflammatory damage to the tubules from GVHD leads to albuminuria and the latter is a manifestation of renal GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In membranous nephropathy, subepithelial immune-complex deposition is present along the glomerular basement membrane. There is also some evidence suggesting that albuminuria is caused by defective tubular trafficking and degradation of albumin 1,2. It may be that in HCT patients, inflammatory damage to the tubules from GVHD leads to albuminuria and the latter is a manifestation of renal GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Newer work postulates that albuminuria results from tubular dysfunction in the trafficking and degradation of albumin 1,2. In both the general population and in cohorts of patients with specific diseases (hypertension, diabetes, inflammatory bowel disease and critically ill patients), albuminuria is a marker for adverse events and poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed evidence for the existence of the degradation pathway has been reviewed elsewhere (26,48,93). Briefly, the degradation pathway is proposed to be a high-affinity/low-capacity pathway, associated with the megalin/cubilin receptor, transporting the relatively small quantities of unretrieved filtered albumin to lysosomes.…”
Section: Major Albumin Processing Pathways In the Proximal Tubular Cellmentioning
confidence: 99%
“…The detailed evidence for the existence of the degradation pathway has been reviewed elsewhere [20,46]. The degradation pathway is proposed to be a high affi nity/low capacity pathway, associated with the megalin/cubilin receptors [47], transporting the relatively small quantities (compared to that fi ltered) of unretrieved fi ltered albumin to lysosomes.…”
Section: Degradation Pathwaymentioning
confidence: 99%
“…Studies by Gekle et al [70] and Russo et al [71] have further demonstrated in PTC cultures that the addition of TGF-β can disrupt albumin uptake and degradation. Studies have demonstrated that quantitative effects of ACEIs in reducing albuminuria can be explained by their ability to activate lysosomal processing [46,72]. In other words, ACEI treatment activates lysosomal activity by inhibiting Ang II production.…”
Section: Albuminuria Derived From Altered Lysosomal Processing Refl Ementioning
confidence: 99%